Risk and productivity change of public sector banks. - Das, Abhimas (2002)
While the relationship between portfolio risk and capital and its interrelationship with operating efficiency has been explored elsewhere limited evidence has been forthcoming on the interrelationships among capital, non-performing loans and productivity. The paper makes an attempt to examine the same in the Indian context. Using data on public sector banks (PSBs) for the period 1995-96 through 2000-2001, the paper finds capital, risk and productivity change to be interwined, with each reinforcing and to a degree, complementing the other. The results imply that inadequately capitalised banks have lower productivity and are subject to a higher degree of regulatory pressure than adequately capitalised ones. Finally, the results lend some credence to the belief that lowering government ownership tends to improve productivity. - Reproduced.
Keywords: Banks